Implementasi Prosedur Audit Laporan Keuangan pada Kegiatan PKL di KAP Erfan dan Rakhmawan: Pengabdian - Surya Rakhmad Aditya; Erfan Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Field Work Practice is a practice-based learning activity that provides students with the opportunity to connect auditing theories obtained in college with real work practices in a Public Accounting Firm. This article aims to describe the assistance in implementing financial statement audit procedures during the Field Work Practice at KAP Erfan dan Rakhmawan. The method used is a qualitative descriptive approach based on assistance activities, with data collected through observation, assisted practice, field notes, and literature study. During the Field Work Practice, the author assisted several technical audit activities under the direction of supervising auditors, including the examination of fixed assets and office stationery inventory at a Community Health Center, the review of income statement documents at a Community Health Center, the review of financing documents at a Sharia Rural Bank, the testing of transactions related to the settlement of accounts receivable in the current period, the observation of cash opname, and the introduction to Microsoft Excel-based ATLAS as a tool for preparing audit working papers. The results show that the assistance in implementing audit procedures was carried out through initial guidance, document examination and data matching, preparation of recapitulations and working papers, and evaluation of work results with the supervising auditors. This activity provided benefits for the author in understanding real audit practices, improving technical skills in document examination, data matching, transaction testing, and preparation of audit working papers, as well as developing professional attitudes such as accuracy, responsibility, discipline, teamwork, communication, and maintaining client data confidentiality.